2013
DOI: 10.1007/s12291-013-0408-y
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline Phosphatase: An Overview

Abstract: Alkaline phosphatase (ALP; E.C.3.I.3.1.) is an ubiquitous membrane-bound glycoprotein that catalyzes the hydrolysis of phosphate monoesters at basic pH values. Alkaline phosphatase is divided into four isozymes depending upon the site of tissue expression that are Intestinal ALP, Placental ALP, Germ cell ALP and tissue nonspecific alkaline phosphatase or liver/bone/kidney (L/B/K) ALP. The intestinal and placental ALP loci are located near the end of long arm of chromosome 2 and L/B/K ALP is located near the en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
412
0
10

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 684 publications
(487 citation statements)
references
References 52 publications
(65 reference statements)
14
412
0
10
Order By: Relevance
“…Again, ALP activity, which is primarily localized in membranes of osteoblastic cells of bones, mammary gland, placental, intestinal mucosa, renal proximal tubules and hepatocytes, where it functions in the alkaline hydrolysis of organophosphates to maintain biological membrane integrity. (Ramaiah, 2007;Dzoyem et al, 2014;Sharma et al, 2014). Thus, Dzoyem et al (2014); Ogbe et al, (2012); Vasudevan and Sreekumari (2007) examined comparatively, the toxicological relevance of ALP activity as a useful indicator of cholestasis and hepatobiliary injury, while ALT and AST activities were essential biomarkers employed for biomonitoring of hepatocellular damage when biological organisms are exposed to stressors From the present study, Table 2 showed increasing serum AST, ALT and ALP activities without significant impact (p > 0.05) among treatment groups relative to control group on exposure to methanolic leaf extract of the plant, suggesting that there was no damage to hepatocyte and renal tissues.…”
Section: Resultsmentioning
confidence: 99%
“…Again, ALP activity, which is primarily localized in membranes of osteoblastic cells of bones, mammary gland, placental, intestinal mucosa, renal proximal tubules and hepatocytes, where it functions in the alkaline hydrolysis of organophosphates to maintain biological membrane integrity. (Ramaiah, 2007;Dzoyem et al, 2014;Sharma et al, 2014). Thus, Dzoyem et al (2014); Ogbe et al, (2012); Vasudevan and Sreekumari (2007) examined comparatively, the toxicological relevance of ALP activity as a useful indicator of cholestasis and hepatobiliary injury, while ALT and AST activities were essential biomarkers employed for biomonitoring of hepatocellular damage when biological organisms are exposed to stressors From the present study, Table 2 showed increasing serum AST, ALT and ALP activities without significant impact (p > 0.05) among treatment groups relative to control group on exposure to methanolic leaf extract of the plant, suggesting that there was no damage to hepatocyte and renal tissues.…”
Section: Resultsmentioning
confidence: 99%
“…Низкая средняя величина отношения кальций/ фосфор в контрольной группе 1 (декортикация по-перечных отростков без использования костно-пла-стического материала) косвенно отражает начальные стадии минерализации в зоне формирующегося кост-ного сращения. Начальные стадии процесса минерализации кост-ной ткани связаны с активацией неспецифичного изофермента щелочной фосфатазы, которая расщеп-ляет органические фосфорсодержащие соединения, увеличивая локальную концентрацию ионов фосфора в везикулах экстрацеллюлярного матрикса до точки насыщения [18]. Щелочная фосфатаза, синтезируе-мая остеобластами, является маркером последних, и ее концентрация в клетках костной ткани коррелирует с их потенциалом минерализации [5], а содержание в плазме крови является информативным показателем костного ремоделирования [15,18].…”
Section: Discussionunclassified
“…ALP is a membrane bound enzyme and responsible for the mineralization of extracellular matrix during differentiation of osteoblast and the formation of new bone [32], and is regarded as an important marker of the differentiation of osteoblast. Figure 5(a) reveals the ALP activities of the different groups.…”
Section: Discussionmentioning
confidence: 99%